Scotch Tape Optical Vapor Sensor for Ethanol–Methanol Mixtures - Angulo Barrios, Carlos (Sensors (Basel), 2019)
A simple optical vapor sensor based on conventional Scotch adhesive tape, for analyzing ethanol–methanol mixtures, is proposed and demonstrated. The sensing signal relies on the variation of optical power transmitted through the tape, resulting from the response of the adhesive material to vapor sorption. The optical sensor exhibits high selectivity for ethanol vapor over methanol vapor. When exposed to vapors from ethanol–methanol liquid mixtures, the sensor shows a linear detection range of 0–100 vol%, and detection limits of 8.8 vol% ethanol and 17.6 vol% methanol. Repeatability, reproducibility, reversibility, and sensitivity to other volatile organic compounds are also studied.